KEMAMPUAN LEKAT RESIN KOMPOSIT PADA REPARASI RESTORASI PORSELEN YANG FRAKTUR - Ali Noerdin (Faculty of Dentistry, Universitas Indonesia, 2015)
Since ceramic and metal ceramic restorations in crown and bridge have the potential to fracture, repairing porcelain restorations has become a serious cosmetic and clinical problem. Composite resins have been the material of choice for porcelain repair intraorally because of the esthetic appearance and easy manipulation. However for the repair to withstand functional load, the bond between the repair material and remaining restoration must be strong and durable. Bond strength between composite resins and dental porcelain have been reported by several authors. Several studies reported that silane solution can significantly improve the bond strength of composite resin to dental porcelain.